Energy efficiency of the bitcoin mining hardware and related blockchain technology - Noor Faiqah Izzati, Afandi (2018)
Nowadays, traders used bitcoin as a platform in making transaction such as exchanging money, without any involvement of a third party or central bank. Bitcoin becomes a phenomenon in this modernization era but the research devoted to the energy efficiency of bitcoins and related blockchain technology is still weakly considered in scientific literature. Especially the energy efficiency for the hardware of bitcoin mining were not considered as a problem in bitcoin mining. The existing approaches in modelling the of bitcoin technology and the hardware of bitcoins were analyzed through this research. The research proposes new formula and algorithm which allows the evaluation of energy efficiency for the hardware of bitcoins mining. MATLAB is used in developing and validation the algorithm. Dataset was selected from open sources and applied in the proposed formula to evaluate and predict energy efficiency of bitcoin mining hardware. Developers of bitcoin hardware systems and bitcoin miners are the possible users of proposed formula and algorithm.